Means Of Motivating the Development of Speech of Students at The Uroks of the Russian Yazyk in the National School (Journal of Pedagogical Inventions and Practices, 2022)
The article describes the motivation of the development of students' speech in Russian language lessons at the national school through incentive sentences. In this case, in the learning process, students learn Russian by following the instructions of the teacher. Students who are forced to understand the purpose of the task in this form automatically correlate their native language with Russian and reproduce the assignment. The use of students' knowledge of the native language is necessary. Therefore, we constantly give examples of incentive sentences in Russian language in conjunction with the native language of students in order to identify common and different languages in the system.